Giant gastric lipossarcoma: case report and review of the literature - Matone, Jacques (Einstein (Sao Paulo), 2016)
Liposarcoma is one of the most common soft tissue sarcomas in adults, occurring in 15 to 20% of all patients with sarcoma. Primary liposarcoma of the stomach is rare. We report a case of patient with giant gastric liposarcoma who underwent surgery after a gastrointestinal bleeding. Preoperative hystopathological diagnosis was not established, even after three biopsy attempts. We discuss differential diagnosis, genetic causes, diagnosis strategies and treatment.